Financial Incentives and Physician Practice Participation in Medicare's Value‐Based Reforms. (26th July 2017) - Markovitz, Adam A.; Ramsay, Patricia P.; Shortell, Stephen M.; Ryan, Andrew M.
Abstract : Objectives: To evaluate whether greater experience and success with performance incentives among physician practices are related to increased participation in Medicare's voluntary value‐based payment reforms. Data Sources/Study Setting: Publicly available data from Medicare's Physician Compare ( n = 1, 278; January 2012 to November 2013) and nationally representative physician practice data from the National Survey of Physician Organizations 3 (NSPO3; n = 907, 538; 2013). Study Design: We used regression analysis to examine practice‐level relationships between prior exposure to performance incentives and participation in key Medicare value‐based payment reforms: accountable care organization (ACO) programs, the Physician Quality Reporting System ("Physician Compare"), and the Meaningful Use of Health Information Technology program ("Meaningful Use"). Prior experience and success with financial incentives were measured as (1) the percentage of practices' revenue from financial incentives for quality or efficiency; and (2) practices' exposure to public reporting of quality measures. Data Collection/Extraction Methods: We linked physician participation data from Medicare's Physician Compare to the NSPO3 survey. Principal Findings: There was wide variation in practices' exposure to performance incentives, with 64 percent exposed to financial incentives, 45 percent exposed to public reporting, and 2.2 percent of practice revenue coming from financial incentives. For each percentage‐point increase in financial incentives, there was a 0.9 percentage‐point increase in the probability of participating in ACOs (standard error [SE], 0.1, p < .001) and a 0.8 percentage‐point increase in the probability of participating in Meaningful Use (SE, 0.1, p < .001), controlling for practice characteristics. Financial incentives were not associated with participation in Physician Compare. Among ACO participants, a 1 percentage‐point increase in incentives was associated with a 0.7 percentage‐point increase in the probability of being "very well" prepared to utilize cost and quality data (SE, 0.1, p < .001). Conclusions: Physicians organizations' prior experience and success with performance incentives were related to participation in Medicare ACO arrangements and participation in the meaningful use criteria but not to participation in Physician Compare. We conclude that Medicare must complement financial incentives with additional efforts to address the needs of practices with less experience with such incentives to promote value‐based payment on a broader scale.